Economic evaluation of the management of municipal firms at the level of rural local self-governments (case study) - Peter Ágh; Roman Vavrek; Marek Dvořák; Viera Papcunová (Economies, 2021)
The municipality generally uses its property to perform self-governing functions, and public or business activities. In the conditions of the Slovak Republic, the municipality operates either as a legal entity in its own name or carries out business activities with the help of a contributory and budgetary organization or business firm established by the municipality. Revenues from business activities form an important part of the revenue of local self-government budgets. The aim of this paper was an economic evaluation of the management of municipal firms at the level of rural local self-governments in the conditions of the Slovak Republic on the basis of selected economic indicators. At the same time, we analyzed the relationship between selected economic indicators in relation to the size, lifespan and number of employees of the firm. The analysis was performed in the time period 2015-2019 on a sample of municipal firms at the level of rural local self-governments. For the analysis, we used selected mathematical-statistical methods (Shapiro-Wilk test, Kruskal-Wallis test, and regression analysis). The analysis showed that the differences in the profitability of municipal firms from the point of view of the region in which they operate as well as from the point of view of the number of employees is not statistically significant. Statistical significance was not demonstrated even within the volume of revenue of municipal firms from the point of view of the region in which the municipal firm operates. The volume of revenues of municipal enterprises with the population of the municipality as well as the length of time of operation on the market is growing, but these are not the only factors on which these results depend.
Keywords: 330; business; economic evaluation; local self-government; municipal firms; rural municipalities